Dynamic modeling and analysis of traction operation process for the shipboard helicopter - Yang, Haojie; Ni, Tao; Wang, Zihe; Wang, Zhilong; Zhao, Dingxuan (Aerospace science and technology, 2023)
The traction operation of a shipboard helicopter on the deck is a complex force-coupling process involving multiple moving entities. To more efficiently simulate the traction process, this study introduces a dynamic model based on the independent modeling of moving subjects (IMMS) method. Initially, the forces on the tire and the articulation part are analyzed, followed by the separate establishment of dynamic models for the helicopter and tractor using the Lagrange equation. Considering the articulated states among the ship, helicopter, and tractor, and according to the active–passive relationships of each entity, a unified solution method is introduced to solve the motion equations sequentially. The model's reliability and real-time performance are subsequently assessed and validated, effectively simulating the helicopter's traction operation procedure. The results reveal that the IMMS dynamic model exhibits high reliability and requires, on average, only 0.5% of the CPU time compared to the conventional dynamic model. The IMMS approach will be useful in advancing research into the modeling of shipboard helicopter traction processes.